Pengembangan Media Pembelajaran Pendidikan Agama Islam Berbasis Augmented Reality Menggunakan Assembler studio - Mardilla, Alifiya (Maliki Interdisciplinary Journal, 2025)
This study aims to design Islamic Religious Education (IRE) learning media based on Augmented Reality (AR) technology through the use of the Assemblr Studio platform. The background of this study stems from the need for innovation in IRE learning, given the low enthusiasm of students in learning and the limited creativity of teachers in utilizing available learning technologies.The development of the media was carried out using a Research and Development (R&D) approach based on the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. This media was designed to deliver PAI material visually and interactively through 3D objects and animations to help students understand abstract concepts more easily. Product validation was carried out by experts, and trials were conducted with teachers and students to measure the feasibility and effectiveness of the media.